A framework for reusable domain specific software component extraction based on demand - Basha, N Md Jubair; Ganapathy, Gopinath; Mohammed, Moulana (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The majority of organizations use an agile software development methodology. Standard analysis and design processes are abandoned due to the enormous demand of generating the product within time and budget. This may result in a lack of high-quality software while components are not constructively reused. The components are identified at a later stage in the majority of component approaches. To address such challenges, a methodology for extracting demand-based domain-specific software components from the repository was developed. The process for reusing current components is described in depth with various domain-specific components, and the suggested framework is for extracting demand-based reusable domain-specific software components.